2013
DOI: 10.1590/abd1806-4841.20132680
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum: skin grafting and hyperbaric oxygen as adjuvants in the treatment of a deep and extensive ulcer

Abstract: Pyoderma gangrenosum is a rare dermatosis of unknown etiology and variable clinical presentation. The disease is challenging for the medical staff, from the frequent diagnostic difficulties to the lack of scientific evidence with a good level to support the management of extensive and refractory cases. Our patient is a 50 year-old man with an extensive and deep ulcer on the left leg, which exemplifies the therapeutic difficulties inherent to the disease and who, fortunately, has progressed with excellent resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Cheng et al, [ 12 ] for example, reported that HBOT reduced the expression of cyclooxygenase-2 and provided brain protection following ischemia. Other typical uses for HBOT include the treatment of extensive ulcers, [ 39 ] including diabetic foot ulcers, [ 40 ] flap [ 41 ] and other organ ischemia, and reperfusion injuries. [ 42 44 ] Hyperbaric oxygen is used because it helps to increase the availability oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al, [ 12 ] for example, reported that HBOT reduced the expression of cyclooxygenase-2 and provided brain protection following ischemia. Other typical uses for HBOT include the treatment of extensive ulcers, [ 39 ] including diabetic foot ulcers, [ 40 ] flap [ 41 ] and other organ ischemia, and reperfusion injuries. [ 42 44 ] Hyperbaric oxygen is used because it helps to increase the availability oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bioengineered skin and dermal substitutes 160 could represent a good alternative option even if specific wide trials are necessary to support their use and cost-effectiveness. The potential benefit of negative pressure wound therapy 161-163 and hyperbaric oxygen therapy 164-166 as adjunctive treatments are also mentioned in small case reports.…”
Section: Methodsmentioning
confidence: 99%
“…However, after the inflammatory process is controlled, large, hard‐to‐heal wounds usually persist, requiring the use of adjuvant therapies, such as skin grafts. The fear of pathergy at the donor site is probably the main reason for the low advocacy of autologous skin grafting in patients with PG …”
mentioning
confidence: 99%
“…Split‐thickness skin grafts (STSGs) may also be performed; however, as it is a procedure comprising a deeper cleavage, the concern of pathergy at the donor site may be greater in comparison with ESGs. More recently, some experience suggested that if the STSG is carried out accompanied by adequate immunosuppression this will lead to improved healing of ulcers with PG . Pichler et al .…”
mentioning
confidence: 99%